Significant Role of Thyroid Stimulating Hormone in the Clinical Activity Score of Thyroid Eye Disease at a Tertiary Hospital in Surabaya, Indonesia - Amatlulloh, Hasna Shahida; Lutfi, Delfitri; Soelistijo, Soebagijo Adi; Prastyani, Reni; Alhakiim, Muhammad Valeri (Folia Medica Indonesiana, 2024)
Highlights: 1. This study, conducted at a tertiary hospital, was the first to analyze the correlation between thyroid status and clinical activity score in thyroid eye disease. 2. This study offers valuable information regarding the crucial role of thyroid stimulating hormone (TSH) in determining the clinical activity score of thyroid eye disease. Abstract Thyroid eye disease is an autoimmune disorder characterized by inflammation of the orbital and periorbital tissues. This condition can lead to vision impairment, which is a notable manifestation of thyroid disease. The symptoms of thyroid disease reflected the level of inflammatory activity, whereas the clinical activity score was indicative of active and inactive phases. This retrospective analysis explored the intricate association between thyroid status and clinical activity score in thyroid eye disease patients, with the hope of providing a foundation for further research on the association between thyroid status and the occurrence of TED. This study utilized medical records from the years 2019 to 2022 from the Outpatient Department of Ophthalmic Oncology of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. The variables examined in this study were thyroid status and the clinical activity score of thyroid eye disease. The statistical analysis was performed using Phi and Cramer's V as well as Spearman's correlation test (p<0.05). A total of 88 patients were diagnosed with thyroid eye disease during the study period. Thyroid eye disease primarily affected female patients (58%) and those who had a mean age of â‰¥41 years (58%). The Phi and Cramer's V analyses indicated no significant association (p > 0.05) between thyroid status and clinical activity score in thyroid eye disease patients. Intriguingly, the results exhibited the presence of euthyroidism as well as both overt and subclinical hypothyroidism and hyperthyroidism, regardless of the clinical activity score. Additionally, the Spearman test that incorporated the levels of thyroid hormones, i.e., triiodothyronine (T3), thyroxine (T4), thyroid stimulating hormone (TSH), and free thyroxine (FT4), showed a significant negative correlation (p<0.05) between TSH and clinical activity score. In conclusion, THS plays a crucial role in determining the clinical activity score of thyroid eye disease patients. This study underscores the imperative for further research to comprehensively elucidate the intricate correlation between TSH and clinical activity score.